2004
DOI: 10.1111/j.1365-2893.2004.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Does an ‘autoimmune’ profile affect the clinical profile of chronic hepatitis C? An Italian multicentre survey

Abstract: Nonorgan-specific autoantibodies (NOSA) are common in patients with chronic hepatitis C virus infection. It is unclear whether serological markers of autoimmunity segregate in a cohort of cases with more severe liver damage. We assessed the relationship between NOSA and demographic, biochemical and histological features in 502 subjects with anti-HCV positive, HCV-RNA positive, HBsAg negative chronic hepatitis consecutively referred to four Italian liver units. Percutaneous liver biopsy was performed in all sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
34
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 26 publications
14
34
5
1
Order By: Relevance
“…Despite the fact that SMAs are often detected in autoimmune hepatitis 39 , these are defined as NOSA because they can also be found, with a variable prevalence, in infectious diseases and some types of tumors 40 . SMAs are most frequently found in patients with HCV, at a prevalence that varies from 13.3% to 66% 6,35,36,41 , which is comparable to the prevalence shown in this study (26.7%). LKM1 is a less common NOSA, with a prevalence ranging from 2.4% in the United States 6 and 2.2 to 8.1% in Italy 35,36, ,which is also consistent with the results presented in this paper (6.8%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the fact that SMAs are often detected in autoimmune hepatitis 39 , these are defined as NOSA because they can also be found, with a variable prevalence, in infectious diseases and some types of tumors 40 . SMAs are most frequently found in patients with HCV, at a prevalence that varies from 13.3% to 66% 6,35,36,41 , which is comparable to the prevalence shown in this study (26.7%). LKM1 is a less common NOSA, with a prevalence ranging from 2.4% in the United States 6 and 2.2 to 8.1% in Italy 35,36, ,which is also consistent with the results presented in this paper (6.8%).…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of NOSA in this study was 24.2%, which is similar to that found in the United States (20.0 to 22%) 6,34 and Europe (25.0 to 36.9 %) 10,[35][36][37] , in which the same dilution was used as the cut-off point (1:40, as recommended for adults) 38 . SMAs are immunoglobulins that react with filaments of the cytoskeleton, including microfilaments (actin and vinculin), Marconcini ML et al -Autoantibody profile in hepatitis C individuals in regards to age, gender, genotype, viral load, comorbidities (diabetes mellitus, hypertension, dyslipidemia and hypothyroidism), serology (HBsAg+, anti-HBc+, anti-HIV+), treatment-naïve status and levels of creatinine, hemoglobin, ferritin, transferrin saturation, AST, ALT, GGT, direct bilirubin and albumin.…”
Section: Discussionsupporting
confidence: 84%
“…Anticardiolipin antibodies have been observed in 3.3% to 22% of HCV patients [77][78][79] . These antibodies were found more frequently in patients with HCV-associated cryoglobulinemia [80] . Our findings are consistent with previously reported data.…”
Section: Discussionmentioning
confidence: 94%
“…According to a recent study, these antibodies do not have any clinical significance in HCV patients, since they are anti-β2-glicoproteinⅠindependent [78] . The auto-antibodies seen in patients with HCV infection appear to resemble those seen in chronic viral infections -the autoantibody titers are low, frequently found during the clinical course of cr yoglobulinemia, but do not produce a typical autoimmune disease [29,80] . The prevalence of thrombocytopenia is higher in patients with chronic HCV infection than in the general population [14] .…”
Section: Discussionmentioning
confidence: 99%
“…A highly favourable treatment response was associated with an absence of ANA and a decrease in SMA titres during therapy. On the other hand, Stroffolini et al [77] found no correlation between NOSAs and the main HCV features or the response to antiviral treatment. These autoantibodies are usually detected in the course of other autoimmune disease which is why the very same should be considered in the differential diagnosis.…”
Section: Autoantibodies Associated With Chronic Hcv Infectionmentioning
confidence: 96%